Chain of ideas : the origins of our authoritarian age - Kendi, Ibram X. (One World, an imprint of Random House, 2026)
"Recall the words chanted in Charlottesville, Virginia: 'You will not replace us!' Recall the string of mass shooters across the globe--in Oslo, Christchurch, Buffalo, El Paso, and Pittsburgh--who claimed their crimes were a defense against 'White genocide.' Recall business and media figures cultivating anxiety and furor over demographic change. These incidents only scratch the surface: Popular and ruling politicians in every region of the world have expressed some version of great replacement theory, eroding democratic norms in the name of preventing demographic change."--Amazon.